KONVERGENSI DAN DIVERGENSI PENDEKATAN TYLER, TABA, DAN OLIVA: TELAAH ANALITIS DAN IMPLIKATIF BAGI KURIKULUM BAHASA DAN SASTRA INDONESIA - Nahdliya Izzatul Mutammimah; Mezeza Putri Handiani; Dedy Irawan; Eka Sofia Agustina; Mulyanto Widodo (STKIP Pesisir Selatan, 2026)
Objective: This academic study compares the fundamental curriculum development models of Ralph W. Tyler, Hilda Taba, and Peter F. Oliva, examining their direct relevance to the modern Indonesian Language and Literature curriculum under the current Merdeka Belajar policy framework. Employing qualitative library research, the study identifies a significant convergence in core curricular structures objectives, content, process, and evaluation ensuring cohesive national quality standards across schools. The primary divergence lies in teacher autonomy. The Merdeka Curriculum specifically adopts Taba’s inductive spirit, granting vital flexibility for localized classroom diagnosis, contrasting with Tyler’s rigid linear approach. Meanwhile, Oliva’s comprehensive model provides an open-system perspective that effectively adapts to dynamic sosiocultural shifts within society. The synthesis of these three classic models strengthens genre pedagogy and multimodal texts in Indonesian language learning. Today's curriculum development represents a hybridization of Tyler's goal clarity, Taba's teacher autonomy, and Oliva's open system. This comprehensive integration successfully fosters systematic yet adaptive learning, ultimately enhancing student literacy and realizing the critical Pancasila Student Profile. Ultimately, it proves that local classroom flexibility can successfully coexist with accountable national standards